Rancang Bangun Sistem Informasi Berbasis Web Pada Lembaga Sosial – Jakarta Timur: Rancang Bangun Sistem Informasi Berbasis Web Pada Lembaga Sosial – Jakarta Timur - Meidina, Meidina Olifia; Dwi Kurniawan , Safar (Applied Information Technology and Computer Science (AICOMS), 2024)
Children's Empowerment and Protection Orphanage The DKI Jakarta Orphanage for the Poor is a government agency in charge of the social sector. One of them focuses on People with Social Problems (PMKS). One method that will be used is the waterfall method. The Annimah Orphanage Program has been computerized by creating a web-based system and providing an office where orphanage administrators and members can manage care efficiently. Testing of this application system uses the black-box testing method. In terms of reporting orphanage data, managers can utilize the Annimah Orphanage Information System website to their advantage. It is hoped that the Annimah Orphanage will attract the interest of donors as a result of the expanded information dissemination of this system..